Upaya Meningkatkan Kemampuan Bermain Alat Musik Anak dengan Pembelajaran Berbasis Kreativitas - Ananda Khairana Sukandar; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Learning is very important in education. Learning activities will determine the achievement of educational goals. Learning in Indonesia is currently based on the 2013 curriculum. However, its implementation is not in accordance with existing concepts. In the Indonesian education system, music learning is an additional learning. Despite being an additional learning, learning music turns out to be able to optimize development in children. The learning methods applied today, namely teacher-centered learning, are not suitable for music learning. Therefore, this study aims to offer learning that can help improve the ability to play music and optimize the goals of music learning. This study uses field observations and practices in data collection. The results of this study are creativity-based learning can explore the potential interests of children's talents, improve children's abilities in the field of music and the process of observation with stages of action can run effectively. Key words: ability, creativity, learning, musical instrument